Evaluasi Kecukupan Panas Proses Pasteurisasi Nata de Coco dalam Kemasan Plastik Polietilen - Hafzialman Hafzialman; Feri Kusnandar; Eko Hari Purnomo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
Sliced nata de coco in light syrup is categorized as an acidified food with an equilibrium pH of 3.3-3.9. Hence, pasteurization process can be applied to kill potential pathogenic and spoilage microorganims in order to produce a safe product and extend its shelf life. The objective of this study was to evaluate the thermal processing adequacy of sliced nata de coco in light syrup (net weight: 2 kg per package; size per slice: 15x15x15 mm2) packed in polyethylene plastic bag (320x230x0.16 mm3) and pasteurized in a conveyor pasteurizer at a heating temperature of 98+2oC for 20 minutes. Thermal process adequacy was determined by comparing the pasteurization value (P) of the process with a standardized P80 value at different D cycles for some microbial targets (2D80, 3D80 and 6D80). The designed pasteurization process satisfactorily inactivated vegetative cells, mold, yeast, Bacillus coagulans, Byssochlamus fulva, and Byssochlamus fulva nivea (Pvalue >P80 value). However, the thermal process was not sufficient to inactivate Alicyclobacillus acidoterrestris, Bacillus polymyxa, Bacillus macerans dan Bacillus pasteurianum (Pvalue<P80 value).